Educação e trabalho : a reforma do ensino técnico-profissional proposta pelo governo federal nos anos 90, no plano global da reestruturação produtiva - Silva, Ivo da (2011)
This research focuses a critical viewpoint about the reform on the technical and professional teaching proposed by the federal government in the 90s, which faced the variety as well as the multiplicity of the formative aspects required by the productive world reorganization and its educational reflexions. In what way these changes affect the school curriculum, the didactic and pedagogical organization of The Federal Institute for Education, Science and Technology of Mato Grosso – IFMT- Campus Cuiabá “Octayde Jorge da Silva”. The reorganization logic and the movement of capitalist production approach, since the manufacturing phase until the current monopolist capitalism, evidence important alterations, marked mainly for the social division and labor techniques, the association of scientific methods in the scope of the business management within the joint of science and technology in the productive environment. Various researches guided this research among them: Frigotto (2002, 2004), Kuenzer (2000,2002,2004), Ciavatta (2005), Machado (1992), Saviani (2004), Ramos (2005), Pochamann (2002) these authors deal with the professional education politics, youth, work and education in Brazil; Nosella (2004), Gramsci (1978), Manacorda (1991), Marx (1857), Sennett (2006), Harvey (1992), Robert (1998) are the ones who discuss the issues related to the historical materialism of the sociology of the work, reorganization and the crisis of the capitalism. The methodology of this study counted on a qualitative approach, which used a case study, having as research instruments: documents analysis, bibliographical study and interviews. The research confirmed the preliminary investigation that the reform created perplexity into the diverse schools segments, in function of new order of the professional education - the relation education-work-market. Indeed, it is an ancient and problematic issue brought by the existence of a theoretician and ideological field of disagreements on the thematic, however, it was observed that after one decade of the implantation of the 2,208/97 Decree the Ministry of the Education that ratified the validity of the respective guidelines, demonstrating agreement with its principles and contents, and, of certain form, reducing the content of Decree N. 5.154/2004. Thus, it was strengthened the idea of that the previous reform was good, but it was not implemented adequately. The study brought out the need of taking ahead a new approach facing the alterations of the LDB, or incorporating into it the missing contents occurred by the approval of Law N. 9,394/96 and Decree N. 2,208/97 whose basic principles were the rights to the laic education, gratuitous, of quality, polytechnical and of omnilateral formation.